Whole genome sequence of Penicillium kloeckeri and insight into its growth-promoting, saline alkaline tolerance properties - Cui, Wenxiao; Wu, Yafen; Ni, Bin; Cao, Jia (Frontiers in Microbiology, 2025)
IntroductionMicrobial agents, mainly bacterial strains, are widely used in agriculture, their often limited efficacy underscores the critical need for resilient fungal alternatives. A novel strain of Penicillium kloeckeri with potential agricultural applications was isolated and purified.Methods and ResultsHere, the genome of P. kloeckeri was sequenced and function predicted. The assembled P. kloeckeri genome had a 34.28 Mb genome size with 41.87% GC content, and revealed functional genes associated with Indole-3-Acetic Acid (IAA), daidzein, siderophore, and organic acid secretion, suggesting its role in plant growth promotion and soil improvement. Metabolite analysis further confirmed daidzein and amino acid production. Under salt stress conditions, P. kloeckeri inoculation (YJKS) significantly improved soybean growth compared to the salt-stressed control (YCK). Specifically, inoculation increased stem diameter by 17.79% and dramatically enhanced root length (99.95%), root area (111.96%), root volume (114.80%), and root biomass (14.97%). Furthermore, in saline alkali soil, P. kloeckeri inoculation effectively reduced soil pH, improve soil physical structure, and enhance nutrient availability.DiscussionP. kloeckeri is a promising new fungal strain with potential agricultural applications. This study provides a foundational genomic resource and initial evidence for its agricultural utility, warranting further investigation into its underlying mechanisms and commercial viability.